Pedicle Screws and Facet Violation - The importance of the Angle between the Facet and the Screw - Rodrigo Amaral; Luiz Pimenta; Angelo Guarçoni Netto; Gabriel Henrique Pokorny; Raquel Fernandes (Revista Brasileira de Ortopedia, 2020)
Abstract Objective To verify whether, regardless of the screw placement technique, there is a safe distance or angle in relation to the facets that can prevent violation of the facet joint when the screws are placed. Methods Retrospective, single, comparative, non-randomized center. We evaluated by axial computed tomography: the angle of the screw/rod in relation to the midline, the angle of the center of the facets in relation to the midline, the distance between the head of the screw/rod to the midline, and the distance from the center of the facets to the midline; the violation of the facet joint will be evaluated in a gradation of 0 to 2. Also will be measured the difference between the angle os the facets and the angle of the screws (Δ Angle) and, the difference between the facet distance and the screw distance (Δ Distance). Results A total of 212 patients and 397 facets were analyzed (196 on the left and 201 on the right). Of these, 303 were not violated (grade 0), corresponding to 76,32%, and 94 suffered some type of violation (grade 1 and 2), corresponding to 23,68%. The mean of Δ angle was 9.87° +/− 4.66° (grade 0), and of 3.77° +/− 4.93° in facets (grade 1 and 2) (p< 0.001), and the Δ mean distance in cases in which there was no violation was 0.94 arbitrary units (a.u.) +/− 0.39 a.u., while the Δ distance in G1 and G2 cases was 0.56 a.u. +/− 0.25 a.u. (p< 0.001). Conclusion The measurements of angle and distance between facet and screw can help in the placement of screws. These parameters can be used as safety measures with the most frequent use of surgical navigation techniques.